Telling Pacific Lives: Prisms of Process - V. Lal, Brij (ANU Press, 2008)
How are Pacific lives imagined, written and read? How are they refracted through prisms of process? From legends about culture heroes to biographies of national leaders, from tales of ancestors to stories of contemporary men and women, from lives told of both the famous and the nameless, this collection of essays - by historians and anthropologists, Islanders and Island scholars - probes questions of personhood, identity, memory, and time across the sweep of the Pacific, as well as practical issues of research and writing.